Regional screen ecosystems at the peripheries: Production and talent development in Tromsø and Aarhus. Issue 2 (1st June 2020) - Chow, Pei-Sze; Sand, Stine Agnete
This article addresses the regionalization of screen culture in Norway and Denmark, focusing on how regional screen entities in Tromsø and Aarhus are working to professionalize production and talent development at the peripheries of both countries. We outline their distinctive characteristics and circumstances as regional hubs and delineate the key actors that constitute the respective screen ecosystems. We focus on the interplay between regional film policy, production and talent development in relation to regional development, geography, creativity, innovation and the economy of culture. Based on an examination of policies, strategy documents and interviews conducted with practitioners in Aarhus and Tromsø over the period 2014‐19, we explore the diverse strategies these regional production hubs employ to develop and ‐ more challengingly ‐ retain talents in the region, arguing that despite the increased attention given to 'diversity' in film policy, structural and cultural obstacles hamper sustainable growth.